Pendampingan Berbasis Keluarga dalam Meningkatkan Dukungan dan Kepatuhan Pengobatan Pasien Tuberkulosis Resisten Obat di Kabupaten Sleman - Sri Arini Winarti Rinawati; Nur Hidayat (Jurnal Kesehatan Pengabdian Masyarakat (JKPM), 2024)
Drug-resistant tuberculosis (DR-TB) remains a major global health challenge with suboptimal treatment success rates. Patients with DR-TB experience not only physical burdens but also significant psychosocial challenges, including stigma, adverse drug effects, and limited social support. Family support plays a crucial role in improving treatment adherence; however, in many settings, such support is not yet structured or systematically implemented. Therefore, a family-based intervention is needed to strengthen support for DR-TB patients. This community-based program employed a quasi-experimental design with a one-group pre-test and post-test approach. The participants consisted of four DR-TB patients and their primary family caregivers in the working area of the Sleman District Health Office, Yogyakarta, Indonesia. A total sampling technique was applied due to the limited population. The intervention included education, counseling, and family mentoring using a flipchart-based educational tool developed based on the Health Belief Model (HBM). Data were collected using structured questionnaires to assess patients’ knowledge and family support before and after the intervention, complemented by observational data. Most patients had a body mass index below 18.5 and experienced multiple adverse drug effects, including nausea, vomiting, gastrointestinal disturbances, and psychological symptoms. Half of the patients reported experiencing social stigma. Baseline assessment showed that 25% of participants had low knowledge, 50% moderate, and 25% high. Following the intervention, there was a noticeable improvement in patients’ and families’ knowledge regarding DR-TB management, family roles, treatment adherence, and coping strategies. Increased family involvement in supporting patients during treatment was also observed. The findings highlight that psychosocial factors, such as stigma, adverse drug effects, and poor nutritional status, significantly influence treatment outcomes in DR-TB patients. The family-based mentoring approach, supported by educational media, effectively improved knowledge and motivation. This approach aligns with the patient-centered care model, emphasizing the importance of family engagement in enhancing adherence and preventing treatment default. Family-based mentoring using flipchart media is effective in improving knowledge and strengthening family support for DR-TB patients. This intervention has the potential to enhance treatment adherence and improve patients’ quality of life. Sustainable programs involving healthcare providers, community health workers, and family engagement, along with innovative educational media, are recommended to strengthen psychosocial support and reduce stigma in the community.